A non-invasive NMR and MRI method to analyze the rehydration of dried sea cucumber. Issue 6 (11th February 2015) - Geng, Shaote; Wang, Huihui; Wang, Xiaoling; Ma, Xiaojun; Xiao, Shan; Wang, Jihui; Tan, Mingqian
Abstract : NMR and MRI were employed to analyze the water uptake and distribution during rehydration processing of lightly dried sea cucumbers. Good linear correlations were observed between the NMR parameters and texture profile analysis. Abstract : Sea cucumbers possess high-value and bioactive components that have been used for human food and pharmaceuticals in treating a wide number of ailments. Most of the sea cucumber products on the market are dehydrated due to the immediate autolysis that occurs upon removal of the sea cucumber from seawater. Rehydration of the dried products is necessary to obtain sea cucumbers with the highest water content. In this study, a rapid and non-invasive NMR and MRI method was introduced to analyze the rehydration process for dried sea cucumber. The spin–spin relaxation time ( T 2 ) weighted NMR signal, obtained by a CPMG pulse sequence and processed by the chemometric method, was used to identify lightly dried and salted dried sea cucumber. The water uptake and distribution during the rehydration process was monitored by NMR 1 H T 2 . Structural changes were analyzed by MRI with T 1 and T 2 weighted imaging. The results indicated that the proper presoaking and rehydration time was 24 and 96 h, respectively, for lightly dried sea cucumber. Good linear correlation during the rehydration process was observed between the NMR parameters and texture profile analysis parameters including the hardness, chewiness, and rehydration ratio of lightly dried sea cucumbers. The NMR and MRI method has the potential to noninvasively analyze the rehydration process of dried sea cucumber.